A note on c-normal subgroups of finite groups - Skiba, A.N. (Algebra and Discrete Mathematics, 2005)
Let G be a finite group. We fix in every noncyclic Sylow subgroup P of G some its subgroup D satisfying 1 < |D| < |P| and study the structure of G under assumption that all subgroups H of P with |H| = |D| are c-normal in G.